A CRITICAL STUDY ON THE CONCEPT OF WELFARE STATE AND WELFARE SCHEMES - Babu, R. Jagadish; Veerraju, Dr. G. (The journal of contemporary issues in business and government, 2023)
The welfare state takes the accountability of security, protection and support of the economic and social well-being of its people. The government gives attention to such people of the state who are not capable of avail themselves of the minimum necessities of a good life. These are mainly like food, cloth, shelter, pension, health insurance etc. It is the moral duty of a welfare state to provide such facilities to the needy sections of the society. The welfare of its citizens remains on the main concern list of the state. Previously, India was not a welfare state because of the foreigner’s autocratic rule. India was not a welfare state under the British rule. They have no equal rights. Even their life is not safe under their rule. Whatever developments British did was in keeping with the benefits of the British colonial government. The industrialization and taxes levied by British government damaged the agro-artisan based economy. It caused poverty in India. Their policies were not in the interests of the people of India. This paper aims to examine the concept of welfare state and welfare schemes.